Histological liver changes in streptozotocin induced diabetic mice - Al-Ani, Imad Matloub Dally; Al-Mishadani, Nu’man S; Muslih, Raad K.; Hamoodi , Salim R. (Kulliyyah of Medicine, International Islamic University Malaysia, 2009)

(untitled)
Streptozotocin (STZ) is selectively toxic to cells in the pancreatic islets. It is well known that STZ causes specific death of B cells and induces diabetes mellitus. This study has been conducted to detect the histological changes that could be induced in liver of adult diabetic mice. The experiments were performed using a single dose of STZ (150mg/Kg. I.P.). Animals were killed two, four and six weeks after injection. The relative percentage of liver weight and liver histology were studied. The results showed several morphological and histological alterations in liver tissues, indicated by increase in the liver percentage of liver weight, glycogen reduction, associated with lipid deposition, inflammatory cells infiltration and Kupffer cells hyperplasia. Furthermore, this study illustrated the worsening of liver histology over a short time in STZ diabetic mice.